Faktor-faktor tekanan emosi di kalangan staf bukan pegawai di Jabatan Pertanian, Petra Jaya, Kuching, Sarawak - Dayang Nur Haida, bte. Abang Saudi (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study is aims to ident(fy the factors affecting the emotional stress among nonexecutive workers at Agricultural Department, Wisma Pelita, Kuching. A total of64 respondents comprising non-executive workers were selected and questionnaires were used as the instrument item. To analyze the data, the researcher used the Pearson Correlation Test from the Statistical Package for Social Sciences (SPSS) version 12.0 sofil-vare. The Pearson Correlation Test is used for analyzing the relevant factors affecting the emotional stress among the staff. This study aims to point out the significant relation between the factors involved; that are work pet:formance, salaries and leadership with emotional stress. For the work performance factors, the result was P = 0.001 (p < 0.01), r = 0.414* which means fair relationship (r = 0.41 0.70). For the salary factor, the result was P = 0.000 (p < 0.01), r = 0.413* which also carries the meaning offair relationship. Lastly, for the leadership factor, the results was p = 0.002 (p < 0.01), r = 0.387* which means poor relationship (0.21 0.40). Thus, the first, second and the third hypotheses are rejected. Based on this finding. the Agricultural Department should give more priority to the emotional stress factors affecting the non-executive workers in the department.